An Evaluation of the Cooperative Strategic Healthcare Plan Training Project Conducted with All Levels of Public Health Officers in Chon Buri - Viriyaprakov, Jurairat (Journal of Health Science of Thailand, 2018)
This research study was aimed to evaluate the cooperative, strategic healthcare plan training project conducted with all levels of public health officers and authorities in Chon Buri. This research applied the CIPP evaluation model focusing on assessing context, input, process, and product. The study was conducted during 1 January - 30 September 2007. The samples were 37 project administrators, 21 lecturers and instructors, and 142 public health officers responsible for healthcare strategic development from Chon Buri Provincial Public Health Center, hospitals, district public health centers, and primary health units. The research instrument was a five-rating scale questionnaire and the results were presented in terms of mean and standard deviation. The findings revealed that in terms of context, the project administrators rated their opinions at the average level concerning congruence between the project objectives and government policies. In terms of input, both lecturers and instructors rated their opinions at a high level concerning sufficiency of the input factors, namely documents, mediums, materials, budget, and cleanliness of training venues and additional services. However, the project organizers, the major and training speakersี knowledge and skills, academic content, training documents were considered moderate. Likewise, the public health officers responsible for healthcare strategic development from the multi-leveled public health centers rated their overall opinions as moderate. Along that line the project administrators rated their opinions on the product at a high level and that the project objectives were eventually achieved. Yet reservations were made in integration of the strategies into health care action plam.